Special paper Diagnostic and therapeutic guidelines in urticaria - Gliński, Wiesław; Silny, Wojciech; Czarnecka-Operacz, Magdalena; Jutel, Marek; Płusa, Tadeusz; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Urticaria is characterized by a complex and diverse aetiology. It is an easy disease to diagnose but identification of elicitating factors as well as treatment present a great challenge for physicians. Each individual patient requires the whole panel of diagnostic procedures including specific provocations, selected according to the clinical characteristics of the case. The first line therapeutic approach is composed of avoidance of triggering factors and treatment of any associated diseases. Symptomatic pharmacological treatment with second generation antihistamines presenting antiinflammatory properties and low adverse effect profile is effective in most patients. In severe nonresponding cases higher doses of antihistamines (up to fourfold) should be applied before switching to selected alternative medications. It should be stressed that systemic treatment with corticosteroids or cyclosporin A because of their unfavourable adverse effect profile is reserved only for severely affected patients.